SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TELLER POOLING TERBAIK PADA PT. BCA Tbk. DENGAN METODE SAW (Simple Additive Weighting) (Jurnal Pilar Nusa Mandiri, 2018)
Human resource management in a company greatly affect many aspects, and as a  determinant of the success of the company, whether it’s on banking company or not. One of the important process in human resource management in a banking company such as PT BCA Tbk. is a selection of the best teller pooling that can spur the spirit of teller pooling to improve the performance and dedication of work. However, with the number of employees who have capabilities that are not much different from one another, sometimes the result of the assessment of each employee is relativity balanced causing difficulty for a boss to determine the right teller pooling as the best teller pooling. Therefore, the Decision Support System is very needed to give a recommendation in making a decision for the selection of the best teller pooling. One of them is by using Simple Additive Weighting Methode (SAW). SAW is a decision support method that uses a weighting summation techniques to obtain the best result of consideration based by alternatives. From the calculation reference to the criteria of tangible, reliability, responsiveness, assurance, empathy that give the result the best teller pooling by an effective calculation using Simple Additive Weighting Methode.
Keywords: Simple Additive Weighting Methode; Decision Support Systems; the best teller pooling